Facile Morphological Qualification of Transferred Graphene by Phase‐Shifting Interferometry - Lee, Ukjae; Woo, Yun Sung; Han, Yoojoong; Gutiérrez, Humberto R.; Kim, Un Jeong; Son, Hyungbin (Advanced materials (Weinheim), 2020)
Post‐growth graphene transfer to a variety of host substrates for circuitry fabrication has been among the most popular subjects since its successful development via chemical vapor deposition in the past decade. Fast and reliable evaluation tools for its morphological characteristics are essential for the development of defect‐free transfer protocols. The implementation of conventional techniques, such as Raman spectroscopy, atomic force microscopy (AFM), and transmission electron microscopy in production quality control at an industrial scale is difficult because they are limited to local areas, are time consuming, and their operation is complex. However, through a one‐shot measurement within a few seconds, phase‐shifting interferometry (PSI) successfully scans ≈1 mm2 of transferred graphene with a vertical resolution of ≈0.1 nm. This provides crucial morphological information, such as the surface roughness derived from polymer residues, the thickness of the graphene, and its adhesive strength with respect to the target substrates. Graphene samples transferred via four different methods are evaluated using PSI, Raman spectroscopy, and AFM. Although the thickness of the nanomaterials measured by PSI can be highly sensitive to their refractive indices, PSI is successfully demonstrated to be a powerful tool for investigating the morphological characteristics of the transferred graphene for industrial and research purposes. Phase‐shifting interferometry (PSI) is successfully demonstrated as a non‐destructive, fast, accurate, and reproducible imaging tool to measure the morphological quality of transferred graphene, compared to conventional imaging tools. Very fine structures, such as graphene wrinkles, various polymer residues on graphene, and tearíng/opening of graphene can be successfully visualized using PSI in a one‐shot measurement within few seconds.